2019
DOI: 10.2147/ott.s230406
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Value Of Apatinib As A Salvage Treatment In Patients With Chemo-Refractory Advanced Cervical Cancer</p>

Abstract: Patients had to have failed at least 2 lines of chemotherapy prior to receiving apatinib. The clinical tumor response was evaluated after 4 weeks of apatinib treatment, and then every 8 weeks (two cycles). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse events were evaluated. Results: Twenty-five patients were included in this study. The median PFS was 5.8 months (95% CI, 4.65-6.95), and the median OS was 12.2 months (95% CI, 8.99-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Some recent research results show that apatinib has a certain effect on cervical cancer. In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer 17,19–21 . In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some recent research results show that apatinib has a certain effect on cervical cancer. In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer 17,19–21 . In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, several studies reported the effect of single‐agent apatinib treatment after failure of first‐line treatment in recurrent or advanced cervical cancer. 17 , 19 , 20 , 21 In 2020, Guo et al 22 assessed the clinical efficacy and safety of apatinib combined with chemotherapy or concurrent chemo‐brachytherapy as first‐line treatment. In comparison to the results from these studies, ORR, DCR and median PFS, and OS of our study seems a slightly higher than those reported in 2019, but lower than the finding from Guo et al in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical trials of advanced or recurrent cervical cancer, the median PFS with pazopanib, lapatinib and sunitinib was 18.1 weeks, 17.1 weeks and 3.5 months, respectively, and the ORR with pazopanib, lapatinib and sunitinib was 9.5, 5.1 and 0%, respectively [14,15]. A comparison between apatinib and other antiangiogenic drugs is shown in Table 5 [2,8,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%